Development and validation of a novel immune-related prognostic model and the potential metastatic mechanism in synovial sarcoma - Huang, Yufeng; Gong, Ming; Lin, Jiaming; Tang, Qinglian; Chen, Hongmin; Hu, Jinxin; Deng, Chuangzhong; Huang, Anfei; Feng, Huixiong; Song, Guohui; Xu, Huaiyuan; Lu, Jinchang; et al. (Frontiers in Immunology, 2024)
BackgroundSeveral clinical trials have shown that immunotherapy plays a pivotal role in the treatment of patients with metastatic synovial sarcoma. Immune-related genes (IRGs) have been demonstrated to predict the immunotherapy response in certain malignant tumours. However, the clinical significance of IRGs in patients with synovial sarcoma (SS) is still unclear.MethodsWe first combined the immune-related ImmPort gene set to search for SS related to metastatic and differentially expressed immune-related genes (DEIRGs) in the GSE40021 dataset from the GEO database. The soft tissue sarcoma database in TCGA was used for univariate Cox regression analyses to identify DEIRGs that were related to overall survival and to build an immune-related prognostic assessment model.ResultsThe study screened a total of six DEIRGs that were closely related to prognosis in metastatic SS. Further analysis showed that there was no significant difference in the expression of several immune checkpoints between the two groups in the GSE40021 data. Moreover, the GREM2 and CTSS genes were significantly expressed in metastatic patients. Further verification of clinical SS tissues from our centre by RT-qPCR analysis demonstrated reduced infiltration of activated NK cells and macrophages but increased M2-type macrophages in metastatic patients. Together, our study successfully constructed an immune-related prognostic assessment model and probably explains the poor efficacy of PD-1 inhibitors for SS patients.ConclusionThe research deepens our understanding of the tumor immune microenvironment and proposes a new immune mechanism for metastatic SS. Early intervention and reversal of immunosuppressive microenvironmental changes are expected to delay metastasis and improve survival.